Analog micromirror-LAPS for chemical imaging and zoom-in application. (August 2015) - Das, Anirban; Yang, Chia-Ming; Chen, Tsung-Cheng; Lai, Chao-Sung
Abstract: The light-addressable potentiometric sensor (LAPS) is a kind of semiconductor-based label-free sensor that is capable of visualizing two-dimensional distribution chemical concentrations above the sensor surface. This report presents a new scanning methodology for the LAPS-based chemical imaging sensor system where an analog micromirror combined with a laser was used as a flexible light-addressing platform. In this set-up, the scanning area and the scanning spatiotemporal resolution can be modified in a user-defined program in a personal computer. This new scanning method can provide a 'zoom-in' applicability to deliver high-resolution chemical images at a desired location. The entire surface of the sensor can be scanned within a few seconds to generate the initial low resolution image; then the area of interest can be selected and scanned with slow speed to produce an image with higher spatial information. The Photo-response-reference bias voltage characteristic, pH-sensitivity and also the chemical imaging of uniform pH buffer solutions are successfully demonstrated with this setup. Highlights: A new scanning methodology based on analog micromirror for LAPS is proposed. It provides a 'zoom-in' and 'zoom-out' scanning facility. Position, step, direction and scanning speed of laser spot are programmable. Chemical imaging using this setup were demonstrated successfully.